Representasi Gender dalam Antologi Cerpen Kitab Kawin Karya Laksmi Pamuntjak - Heni Rugun Siregar; Liza Septa Wilyanti; Ulil Amri (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to represent female characters in the short story anthology